Advantages, Risks, and Prospects of Kazakhstan’s Accession to the Multi-Party Interim Appeal Arbitration Arrangement (MPIA) - Sayenko, L.P. (Кұқық және мемлекет, № 1 (106), 2025)
The paralysis of the Appellate Body has disrupted the appellate review process in Word Trade Orga- nization (WTO) dispute settlement system, undermining the ability of the members to resolve trade disputes. In response, some members introduced appellate arbitration through the Multi-Party Interim Appeal Arbitration Arrangement (MPIA) in 2020. Given Kazakhstan’s participation in the WTO, this article aims to examine Kazakhstan’s approach to the Appellate Body dysfunction and evaluate the proce- dural features, advantages, and limitations of appellate arbitration and its implications for Kazakhstan. To achieve this, the study employs general scientific, dogmatic, statistical, and legal interpretation methods to assess Kazakhstan’s role in WTO dispute settlement and its potential engagement with the MPIA. The study focuses on Kazakhstan’s stance on international trade disputes, particularly its engagement with the WTO’s dispute settlement mechanism as a subject. As a key aspect of its novelty, this article offers a com- prehensive analysis of Kazakhstan’s position regarding the MPIA, emphasizing underexplored factors, considering its trade partnerships, historical participation in disputes, and broader economic strategy within the WTO framework. The conclusion is that, while appellate arbitration offers a pathway to resolve disputes and enhance fairness in the WTO system, the analysis suggests that Kazakhstan has stronger reasons to refrain from the MPIA membership. Key factors include the absence of Kazakhstan’s major trading partners – such as Russia and China – among the MPIA members and Kazakhstan’s ‘passive role’ in WTO disputes, mainly presented as a third party. Additionally, Kazakhstan’s transition out of ‘special and differential treatment’ eligibility diminishes the practical benefits of MPIA membership. Instead, the article argues that Kazakh- stan could adopt a strategic approach by joining ad hoc appellate agreements only when the risk of being involved as a party to the dispute occurs, thereby protecting its interests.
Keywords: WTO, Appellate Body, dispute settlement, MPIA, international trade, reform, trade stability